Sistema contable administrativo y su incidencia en las operaciones de la Empresa de productos forestales S.A. Emproforsa del cantón Valencia, año 2011. propuesta de un manual contable – administrativo - Guzmán Macías, María del Carmen (2012)
This research shows the contribution in the framework of the administration of the accounting area, highlighting the accounting information system for its importance and interest for companies, which is in charge of collecting and summarizing the objective and relevant information of the economic events produced in the organization The company EMPROFORSA, with the application of the accounting system, carries out a process of registration, measurement and presentation in monetary terms, of all the operations carried out in the company, controlling compliance with policies, plans, programs and administrative processes by making available to the high manages a set of goods, rights and objects, in order to comply with the objectives set in the company in conjunction with the collaborators, among which the most notable are: 1) Develop an information system for decision-making that respects the legal framework of the EMPROFORSA Company 2) Satisfy the needs at the lowest possible cost, 3) Explain to what extent the management has caused damage or increase in the operation of the company For this reason, it is essential to use accounting manuals as the main instrument to achieve effective high-level business management in order to obtain a solid organization in administrative accounting processes that allows the Empresa de Productos Forestales S.A. EMPROFORSA, apply economic and financial information in the presentation of financial statements. x This strategic use of financial statements strengthens decision-making to management and provides job tranquility to employees since it contributes to institutional improvement and therefore makes it possible to act in emergent situations with operational efficiency by presenting timely information to the members of the company. for immediate decision making and timely link with customers